A DETERMINATION OF THE NEON ISOTOPIC COMPOSITION OF THE DEEP MANTLE - Yokochi R.; Marty B. (My University, 2004)
The neon isotopic composition of the deep mantle, which allows to investigate formation processes of the Earth, is subject to debate. We have analyzed Ne trapped in fluid inclusions from plume-related Devonian rocks from the Kola Peninsula, Russia. The lower limit for pristine neon in the deep mantle is set at 20Ne/22Ne≥13.0±0.2, close to the solar wind (SW) value. We interpret this similarity as evidence that mantle light noble gases were directly incorporated from the solar nebula rather than derived from implanted meteoritic solar component, possibly through gravitational capture of a proto-atmosphere. This constraint is consistent with geochemical observations of rapid accretion of a major part of the growing Earth within the inferred lifetime of the solar nebula. If depleted mantle neon admits an upper limit of 12.5, then the occurrence of plume type neon with 20Ne/22Ne≥13.0±0.2 may indicate a primordial Ne heterogeneity in the mantle. The 3He/22Ne ratios of terrestrial mantle reservoirs sampled by MORB and plumes vary with the degree of volatile element depletion of the mantle. This correlation was possibly established during magmatic events having led to the chemical characteristics of the depleted mantle reservoir.